Penguatan Moderasi Beragama Mahasiswa melalui Kegiatan Tutorial Keagamaan di Perguruan Tinggi Umum - Nasrudin, Ega; Anwar, Saepul; Islamy, Mohammad Rindu Fajar (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
This study aims to analyze the strengthening of religious moderation of students through religious tutorials at state universities to ward off radicalism. The research method uses a sequential design of mixed method explanation. Quantitative data was collected by random sampling with a sample of 809 people. Qualitative data was conducted by interviews using purposive sampling to a number of related parties, observation records, dan documentation studies. The average score of religious moderation after participating in tutorial activities was higher than the average score of religious moderation of students before participating in religious tutorial activities. This finding is supported by the results of a significant t-test (sig. 0.000). The dimension of religious moderation that experienced the largest increase was national commitment (4.29%), followed by accommodating to local culture (3.60%), non-violence (3.37%), dan tolerance (3.12%). This increase is influenced by the internalization of values dan examples from lecturers, tutors, dan fellow students. However, most students only showed a low increase in moderation due to having had a prior understanding of religion dan the constraints of the absence of tutors during mentoring. This research emphasizes the importance of the role of religious tutorials in shaping students' religious moderation attitudes.